2015
DOI: 10.1007/978-3-319-16178-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Nature Conservation Drones for Automatic Localization and Counting of Animals

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 32 publications
0
92
0
Order By: Relevance
“…Several of the above-cited studies attempted, with varying degrees of success, various digital image analysis techniques for automated detection and (or) counting of animals (Abd-Elrahman et al 2005;Selby et al 2011;Chabot and Bird 2012;Grenzdorffer 2013;Maire et al 2013;Christiansen et al 2014;van Gemert et al 2015). Numerous additional examples of similar automated analysis techniques applied to imagery acquired by conventional aircraft are available in the broader wildlife literature (e.g., Laliberte and Ripple 2003;Descamps et al 2011;Groom et al 2013).…”
Section: Herptilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several of the above-cited studies attempted, with varying degrees of success, various digital image analysis techniques for automated detection and (or) counting of animals (Abd-Elrahman et al 2005;Selby et al 2011;Chabot and Bird 2012;Grenzdorffer 2013;Maire et al 2013;Christiansen et al 2014;van Gemert et al 2015). Numerous additional examples of similar automated analysis techniques applied to imagery acquired by conventional aircraft are available in the broader wildlife literature (e.g., Laliberte and Ripple 2003;Descamps et al 2011;Groom et al 2013).…”
Section: Herptilesmentioning
confidence: 99%
“…Finally, UAS have detected orangutan (Pongo abelii) nests in treetops (Koh and Wich 2012;van Gemert et al 2015) as well as northern pocket gopher (Thomomys talpoides) mounds in grasslands . Christiansen et al (2014) demonstrated automatic detection of rabbits in thermal imagery captured from a lift, intended to simulate a low-flying UAS scanning for small concealed animals in the path of agricultural machinery.…”
Section: Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the terrestrial world, UAVs have been used for a wide variety of conservation applications (van Gemert et al, 2014;Gonzalez et al, 2016). Some examples include, counting elephants (Loxodonta africana) (Linchant et al, 2013;Vermeulen et al, 2013), UAV surveillance (anti-poaching tools) for elephants and rhinoceros (Diceros bicornis and Ceratotherium simum) (Marks, 2014;MuleroPázmány et al, 2014;Hahn et al, 2017), locating chimpanzee nests (Pan troglodytes) (van Andel et al, 2015) and mapping Sumatran orangutan (Pongo abelii) habitat, distribution and density Szantoi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[56,87,110,119] for a selection of such projects. A project targeted directly at anti-poaching of rhinoceros is presented in [90], where an unmanned aerial system was deployed in the KwaZulu-Natal province in South Africa.…”
Section: Savanna Applicationmentioning
confidence: 99%